Hospital solid waste management system of the CLAS Ciudad Nueva - Tacna Health Center, 2016 - Quispe Cruz, Cristian Simón (2017)
This study aims to analyze the Hospital Solid Waste Management System and propose strategic points for the elaboration of a Hospital Solid Waste Management Plan. The survey was used as an instrument to evaluate the knowledge of all health center staff about the content of standards and waste management, i¡dentifying those areas and risky procedures practiced in the health center Clas New city. This work was framed within a descriptive research of transversal type, the applied design ¡s the non experimental one, the unit of study was the total conform 89 workers. It was evidenced that 91% of the personnel have knowledge about the management of solid waste hospital, with respect to the risks of the 95.5% management if they know, regarding the knowledge about the segregation of the RSH 83.10%if they know. Regarding the application to Technical Standard No. 096-MINSA / DIGESA V.01. Technical Standard of Health Management and Solid Waste Management in Health Facilities and Medical Support Services, 65.2% of the staff do not know the content of this standard, a situation that ¡is reflected in some areas of the health center. The lack of training commitment and the development of a management plan for solid waste management would improve the solid waste management system at all levels and the implications for environmental control.